Polyphenols by Generating H2O2, Affect Cell Redox Signaling, Inhibit PTPs and Activate Nrf2 Axis for Adaptation and Cell Surviving: In Vitro, In Vivo and Human Health - Joseph Kanner (MDPI AG, 2020)
Human health benefits from different polyphenols molecules consumption in the diet, derived mainly by their common activities in the gastrointestinal tract and at the level of blood micro-capillary. In the stomach, intestine and colon, polyphenols act as reducing agents preventing lipid peroxidation, generation and absorption of AGEs/ALEs (advanced glycation end products/advanced lipid oxidation end products) and postprandial oxidative stress. The low absorption of polyphenols in blood does not support their activity as antioxidants and their mechanism of activity is not fully understood. The results are from in vitro, animal and human studies, detected by relevant oxidative stress markers. The review carries evidences that polyphenols, by generating H2O2 at nM concentration, exogenous to cells and organs, act as activators of signaling factors increasing cell Eustress. When polyphenols attain high concentration in the blood system, they generate H2O2 at µM concentration, acting as cytotoxic agents and Distress. Pre-treatment of cells or organisms with polyphenols, by generating H2O2 at low levels, inhibits cellular PTPs (protein tyrosine phosphatases), inducing cell signaling through transcription of the Nrf2 (nuclear factor erythroid 2-related factor 2) axis of adaptation and protection to oxidation stress. Polyphenols ingestion at the right amount and time during the meal acts synergistically at the level of the gastrointestinal tract (GIT) and blood system, for keeping the redox homeostasis in our organism and better balancing human health.